A study to find out the association between duration of preterm premature rupture of the membrane’s delivery interval and maternofetal complications - Saraswathy, Anusree; Ravindran, Ajitha; Vaman, Jayshree V.; Brahmanandan, Mayadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The main maternal complications of preterm premature rupture of the membranes (PPROM) are chorioamnionitis, puerperal pyrexia, abruption and the neonatal complications are neonatal sepsis, congenital pneumonia, neonatal ICU stay and neonatal death. The aim of the study is to find out the association between duration of latent period in PPROM i.e. the time period between rupture of membrane to delivery and maternofetal complications. Methods: The present study was a Prospective observational study conducted on 240 preterm antenatal women with PPROM in the Department Obstetrics and Gynecology, SATH, GMC, Thiruvananthapuram. The gestational age at rupture of membranes, latent period from time rupture of membranes to delivery, gestational age at time of delivery and the maternal and neonatal outcome were compared and subjected to statistical analysis. Results: Maternal chorioamnionitis in the group with PPROM delivery interval between 2-7 days (79.3%) whereas there were (13.8%) in which PPROM delivery interval was less than 24 hrs. Puerperal pyrexia in 2-7 days delivery interval was 11.3% and in <24 hrs were 2.6%. Neonatal sepsis in 2-7 days was 28.3% and 12.5% in<24 hrs. Congenital pneumonia in 2-7 days was 16.9% and in<24 hrs was 11.6%. Conclusions: In the present study membrane rupture between 28-34 weeks gest age and latency period. 2-7 days were associated with high incidence of maternal chorioamnionitis, puerperal pyrexia congenital pneumonia, early onset neonatal sepsis and neonatal death. Undue prolongation of pregnancy may increase the risk of chorioamnionitis, neonatal sepsis and neonatal deaths.